1967
DOI: 10.3758/bf03330792
|View full text |Cite
|
Sign up to set email alerts
|

Punishment continuity and self-punitive behavior

Abstract: Partial punishment schedules (20% or 50% trials punished) are as effective as 100% punishment in generating and maintaining self-punitive behavior following avoidance training. If punishment is not continued. running extinguishes fairly quickly.After a ratlearns an avoidance running response, punishment given in the last section of the alley before the goal box is similar in some respects to the avoidance training shock. Given a few avoidance training trials, the animal is usually well on the way to the goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1968
1968
1980
1980

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The results of the present study confirm the earlier fmdings of Babb and Hom (1971) and Hom and Babb (1975), who found that rats punished in the goalbox during extinction ran significantly faster than rats not shocked during extinction. In addition, the data support the findings of Beecroft, Fisher, & Bouska (1967), Gwinn (1949), and Martin and Moon (1968), who, using an alley shock punishment procedure , found that percent of punished extinction trials had no substantial effects on the magnitude of the self-punitive effect. It may also be noted that, while Melvin(1964) reported extinction run speeds to be an increasing function of percentage of punished trials, the punished groups did not differ significantly among themselves, and only a nonsignificant trend of increased run speed with increased percent of punishment was observed.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The results of the present study confirm the earlier fmdings of Babb and Hom (1971) and Hom and Babb (1975), who found that rats punished in the goalbox during extinction ran significantly faster than rats not shocked during extinction. In addition, the data support the findings of Beecroft, Fisher, & Bouska (1967), Gwinn (1949), and Martin and Moon (1968), who, using an alley shock punishment procedure , found that percent of punished extinction trials had no substantial effects on the magnitude of the self-punitive effect. It may also be noted that, while Melvin(1964) reported extinction run speeds to be an increasing function of percentage of punished trials, the punished groups did not differ significantly among themselves, and only a nonsignificant trend of increased run speed with increased percent of punishment was observed.…”
Section: Resultssupporting
confidence: 86%
“…Previous studies examining the effects of periodic punishment, which applied punishment in different parts of the alley but not in the goalbox, have yielded mixed results. Several studies (Beecroft , Fisher, & Bouska, 1967;Gwinn, 1949;Martin & Moon, 1968) found that rats given different schedules of punished extinction respond similarly to rats given punishment on every extinction trial. In contrast , Bender and Melvin (I967)…”
Section: Effects Of Percentage Of Goal-punished Extinction Trials On mentioning
confidence: 99%
“…Melvin (1964) found self-punitive behavior more likely to occur with higher percentages of punishment after 33% or 67% schedules of "partial reinforcement" escape trials during acquisition. Beecroft, Fisher, & Bouska (1967) report self-punitive behavior to be equally probable within 20, 50, and 100% schedules of punishment after avoidance training. Thus, while different training procedures were employed in the two studies (escape vs avoidance), the effects of percentage of punishment have been different.…”
mentioning
confidence: 99%